Immunometabolism of Phagocytes and Relationships to Cardiac Repair - Zhang, Shuang; Bories, Gael; Lantz, Connor; Emmons, Russel; Becker, Amanda; Liu, Esther; Abecassis, Michael M.; Yvan-Charvet, Laurent; Thorp, Edward B. (Frontiers in Cardiovascular Medicine, 2019)
Cardiovascular disease remains the leading cause of death worldwide. Myocardial ischemia is a major contributor to cardiovascular morbidity and mortality. In the case of acute myocardial infarction, subsequent cardiac repair relies upon the acute and coordinated response to injury by innate myeloid phagocytes. This includes neutrophils, monocytes, macrophage subsets, and immature dendritic cells. Phagocytes function to remove necrotic cardiomyocytes, apoptotic inflammatory cells, and to remodel extracellular matrix. These innate immune cells also secrete cytokines and growth factors that promote tissue replacement through fibrosis and angiogenesis. Within the injured myocardium, macrophages polarize from pro-inflammatory to inflammation-resolving phenotypes. At the core of this functional plasticity is cellular metabolism, which has gained an appreciation for its integration with phagocyte function and remodeling of the transcriptional and epigenetic landscape. Immunometabolic rewiring is particularly relevant after ischemia and clinical reperfusion given the rapidly changing oxygen and metabolic milieu. Hypoxia reduces mitochondrial oxidative phosphorylation and leads to increased reliance on glycolysis, which can support biosynthesis of pro-inflammatory cytokines. Reoxygenation is permissive for shifts back to mitochondrial metabolism and fatty acid oxidation and this is ultimately linked to pro-reparative macrophage polarization. Improved understanding of mechanisms that regulate metabolic adaptations holds the potential to identify new metabolite targets and strategies to reduce cardiac damage through nutrient signaling.